Parametric investigation of 3D RC beam–column joint mechanics - Alaee, Pooya (2015)
This paper presents the experimental and numerical findings of interior and exterior beam–column–slab joints under cyclic lateral loading in two orthogonal directions. Two full-scale interior and one exterior beam–column joint assemblies incorporating floor slabs were subjected to quasi-static cyclic loading and zero column axial loads. The test results from these three models, designed according to building code provisions for ductile moment-resisting frames, were satisfactory in terms of strength and ductility capacity. Parametric studies via the non-linear finite-element approach were performed to study the influence of various parameters on the strength and ductility of three-dimensional beam–column joints. The study confirmed the beneficial effects of incorporating floor slabs and transverse spandrel beams on the behaviour of beam–column joints. The presence of axial compressive load improved the joint shear capacity of the beam–column joints, but a threshold limit should be applied.